ESTIMATION OF GENETIC DIVERSITY WITHIN AND AMONG PULAI (Alstonia scholaris (L.) R. Rr.) PROVENANCE REVEALED BY RAPD MARKER - Dwi Hartati; Anto Rimbawanto; Taryono Taryono; Endang Sulistyaningsih; AYPBC Widyatmoko (Center for Forest Biotechnology and Tree Improvement (CFBTI), 2007)
Pulai (Alstonia seholaris (L.) R. Br.) is species of high economic value and has been intensive utilization. Conservation effort and breeding strategies should be carried out prevent extinetion. The study ofgenetic diversity using RAPD marker can asses polymorphism through bandingpatterns from amplified DNA. The aims of this research are to estimate genetic diversity within and among pulai populations, investigate distribution ofgenetic diversity, and genetic relationship between pulai provenance. Leaf samples were taken from eighteen pulai provenances in Indonesia, namely Lubuk Linggau, Pendopo, Benakat, Banten, Bantul, Gunungkidul, Bali, Purworejo, Perawang, Mataram, Sumbawa, Kupang, Timor Tengah Selatan, Agam, Gowa, Makassar, and Kendari. Genetic diversity was analyzed using 23 primers and produced 114 polymorphic loci. Results showed that the distribution ofgenetic diversity within provenance was higher than that of among provenance. Cluster analysis revealed that the eighteen provenances was into two major groups. The first group consisted of provertance Lubuk Linggau, Banten and Pendopo. The second group of provenance of Benakat, Perawang, Agam, Solok, Bali, Kendari, Bantul, Purworejo, Gunungkidul, Mataram, Sumbawa, Gowa, Makassar, Kupang, and Timor Tengah Selatan. In general, the genefic relationships among eighteen provenances donot show the relation between genetic diversity and geographic distribution of pulai provenance.